Associated factors for maternal-foetal complications in pregnant women with sickle cell disease at the departmental University Hospital of Borgou and Alibori (Benin) - Vodouhe, Mahublo V.; Obossou, Awade A.; Mohamed, Falilatou A.; Ahouingnan, Fanny M. H.; Chogou, Justin Y.; Atade, Raoul; Imorou, Rachidi S.; Agossou, Joseph (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Sickle cell disease is one of the most common genetic disorders in the world, with a high prevalence in Africa. It is a pathology that threatens the maternal-fetal prognosis in case of pregnancy. The objective of this study was to describe the maternal-foetal complications and to identify the factors associated with maternal-foetal complications in sickle cell pregnant women (SP). Methods: This was a descriptive cross-sectional study with retrospective data collection over a period of 4 years (01 January 2015 to 31 August 2019). The study population was All SP who had given birth in the maternity ward of the UH of Borgou/Alibori. Results: We recorded 130 SP out of 10087 admissions, either a frequency of 1.3%. There were 119/130 exploitable files. Maternal complications during pregnancy were: vaso-occlusive crises 79%; severe anaemia 27.7%; hyponatremia 10.1%; vasculo-renal syndromes 18.4%; infections 74.8%. The foetal complications during pregnancy were: Preterm births 38.6%, in utero deaths 17.6%, low birth weight 54.7%. Early neonatal mortality was 8.4% (8/95). There was a 4.2% (5/119) of maternal deaths. Low educational level of the SP, SS genotype, insufficient antenatal follow-up and antenatal follow-up outside the specialized center for the care of sickle cell pregnant women (SCCSP) were the factors associated with maternal-foetal complications in the SP. Conclusions: The association of pregnancy and sickle cell disease is frequent in West Africa, particularly in Benin, and is characterised by numerous maternal-foetal complications that are associated with certain factors.